A Characterisation of Setswana Complex Sentences. Issue 2 (4th May 2018) - Letsholo-Tafila, Rose
ABSTRACT: This article investigates clause linkage in Setswana arguing that, just like in other languages of the world, Setswana complex sentences cannot be classified simply into coordinate and subordinate structures. Using syntactic evidence such as scope facts (involving modality/mood, tense and polarity) as well as morphological evidence, we demonstrate that conjoined clauses in Setswana can be classified into three nexuses, namely coordination (which involves two independent junctures, with one involving a conjunction and the other involving juncture juxtaposition); cosubordination (which involves three types of dependencies: structural, morphological and operator dependency), and subordination (in which a dependent clause is embedded in the main clause, e.g. subject and object complement sentences; relative clauses; sentential and adverbial modifiers). The analysis in this article is guided by Role and Reference Grammar theory.